Modeling and control of a wheelchair considering center of mass lateral displacements - Andaluz, Víctor (2015)
This work presents the kinematic and dynamic modeling of a humanwheelchair system where it is considered that its mass center is not located at the wheels’ axis center of the wheelchair. Furthermore, it is presents a new motion controller for human-wheelchair system that is capable of performing positioning and path-following tasks. The proposed controller has the advantage of simultaneously performing the approximation of the robot to the proposed path by the shortest route and limiting its velocity. This controller design is based on two cascaded subsystems: a kinematic controller with command saturation, and a dynamic controller that compensates the dynamics of the robot. © Springer International Publishing Switzerland 2015.